Terrorism and Islam in the Global Perspective - Mestika, Hana Fairuz (Faculty of Law Universitas Negeri Semarang, 2023)
Regarding terrorism, it is endless if discussed further. Nowadays the world or the international community often considers that Muslims are terrorists, and in their minds, they have been imprinted if there is a crime of terrorism, surely Muslims are the perpetrators. Even though it is a very, very big mistake. Muslims are never taught to be terrorists, they are never taught or educated to be criminals. Many in the international community do not want to make friends with people who convert to Islam because they are afraid. Why do so many people misinterpret the radical movement and relate to the religion of Islam. Of course, this is not true. We as a young generation must change the existing mindset, which has been imprinted in many of the thoughts of the international community regarding terrorism itself. In fact, terrorism is a criminal act that is currently the most troubling criminal offense in the world.